Learning From Instructional Videos: Learner Gender Does Matter; Speaker Gender Does Not - Schrader, Claudia; Seufert, Tina; Zander, Steffi (Frontiers in Psychology, 2021)
One crucial design characteristic of auditory texts embedded in instructional videos is the speaker gender, which has received some attention from empirical researcher in the recent years. Contrary to the theoretical assumption that similarity between the speaker’s and the learner’s gender might positively affect learning outcomes, the findings have often been mixed, showing null to contrary effects. Notwithstanding the effect on the outcomes, a closer look at how the speaker’s gender and speaker–learner similarities further determine cognitive variables, such as different cognitive load types, is overdue. Moreover, on the part of the learner, the role of situational interest in the learning topic that might be gender related has been neglected so far. Therefore, this study explored the role of speaker and learner gender and their interaction regarding learning outcomes. We broaden our perspective by investigating the effects of gender-related differences concerning situational interest in the topic being taught and by determining different types of cognitive load. In a 2 (female/male speaker) × 2 (female/male learner) within- and between-subject design, 95 students learned about female and male human sexual maturity with an instructional video containing auditory explanations. Analysis results indicate that speaker gender and speaker–learner gender similarity had no impact on learning gains, situational interest, and cognitive load types. However, the results demonstrate that learner’s gender, especially for the topic of female sexual maturity, matters the most in line with the assessed variables. Compared with males, females had higher learning gains, reported higher interest in the topic, and invested more germane cognitive resources. Thus, instructional designers may want to consider learner gender-dependent interest and how it can be triggered when creating videos with auditory explanations.